USE OF SIMULATION METHODS AND VIDEO MEDIA TEACHING IN INCREASING STUDENTS' INTEREST TO BECOME TEACHERS (Case in Economics Learning Strategy Course) - Neti Budiwati; Kinanti Geminastiti H; Fazar Nuriansyah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The problem of the low interest in being a teacher for students participating in the Economics Learning Strategy Study Program of Economics Education Study Program at the University of Economics Education became the motivation for this research to be carried out. This study aims to determine whether the use of teaching simulation methods and teaching video media for teachers can increase students' interest in being a teacher. The research method is descriptive qualitative with an open questionnaire data collection tool through the Integrated Online Learning System (SPOT) Universitas Pendidikan Indonesia. The research subjects were 88 students participating in the Economics Learning Strategy course. The results showed that the student's interest in becoming a teacher after lectures using teaching simulation methods and teaching video media was on average in the high classification, and a change in interest in becoming a teacher was 80.62%. It can be concluded that the use of teaching simulation methods and teaching video media in the Economics Learning Strategy course increases students' interest in becoming teachers.